Consumer Perception towards Organised Vs Unorganised Retailing for FMCGs & Grocery - Khosla, Dimple (Gyan Management Journal, 2016)
Fast Moving Consumer Goods like soaps, shampoos, detergents, biscuits etc and Grocery items are the basic needs for which consumer goes very frequently to the market. As we all know that organized format of retail sector also exists along with the traditional format of retail sector in the form of local kiryana stores. This paper is just an attempt to see that for these frequent demands which format of retail sector people prefer to visit. What are the various factors that affect their choice of format and to see whether there is any significant difference in the choice of format on the basis of age, gender and income level. An attempt has also been made to see whether going to organized format has increased their level of spending or not. For this purpose a sample of156 consumers from Haryana State has been taken. To analyze simple average and chi square test have been used. Diagrammatic representation is also used wherever required.